Spectral responsivity measurements of DSSC devices at low chopping frequency (1 Hz). (30th October 2014) - Bardizza, Giorgio; Pavanello, Diego; Müllejans, Harald; Sample, Tony
Abstract: Dye‐sensitized solar cells (DSSCs) are generally known to possess a slow response time for photocurrent generation by incident light. Electrical power measurements can only be accurately made if sufficient time is allowed to complete photocurrent generation, in contrast to the case of c‐Si solar cells. There are two methods which can satisfactorily measure the spectral responsivity (SR) of DSSCs, i.e. the "AC method" and "DC method". Of these two, the AC method in the IEC 60904‐8 standard is the normal procedure for SR measurement of solar cells. A new setup implemented at ESTI for the SR measurement of DSSCs is presented, making use of a low frequency (≤1 Hz) chopped monochromatic beam produced from a continuous broadband light source with band‐pass filters and lock‐in technique for measurements of the signals. The beam is projected onto the device under test (DUT) and superimposed over continuous white bias light. The procedure for the determination of the absolute SR is presented, and the influence of the slow response for photocurrent generation typical of DSSC devices is investigated. The results obtained with the new setup for standard c‐Si solar cells and DSSCs are reported and discussed, providing a validation of the system. © 2014 The Authors. Progress in Photovoltaics: Research and Applications published by John Wiley & Sons, Ltd. Abstract : A new validated setup was implemented at ESTI for spectral responsivity (SR) measurements of photovoltaic devices with slow response for photocurrent generation as dye‐sensitized solar cells (DSSC). It was able to run reliably SR measurements of DSSCs at low chopping frequency (1 Hz). The procedure for the determination of the absolute SR is presented, and the influence of the slow response of DSSC devices is investigated.